Role of prophylactic hemoclip placement in prevention of delayed post-polypectomy bleeding for large colon polyps: a meta-analysis of randomized controlled trials - Gangwani, Manesh Kumar (Ann Gastroenterol, 2021)
BACKGROUND: Polypectomy is a widely used and effective procedure to treat precancerous polyps. Delayed post-polypectomy bleeding (DPPB), a common complication of polypectomy, may diminish the utility of this procedure. Previous data on the efficacy of hemoclips has been conflicting, therefore we aimed to collectively evaluate and analyze the data to reach a definitive conclusion on the efficacy of using hemoclips to prevent incidences of DPPB in patients with large polyps (≥10 mm). METHODS: We identified a total of 261 studies based on our previously defined search strategy. After screening, we included 6 randomized controlled trials. A meta-analysis was performed comparing the use of prophylactic application of hemoclips to a standard group without prophylactic clip placement for large polyps. RESULTS: We found a statistically significant reduction in the incidence of DPPB when using hemoclips for large polyps. The overall incidence of DPPB was lower in the hemoclip group compared to the standard group for all large polyps ≥10 mm (relative risk 0.51, 95% confidence interval 0.35-0.75; P=0.01; I(2)=0%). CONCLUSIONS: The use of hemoclips in achieving hemostasis for large polyps has a beneficial effect and appears to prevent DPPB. This reinforces the routine clinical practice of using hemoclips in polypectomy procedures.